The “Cast Iron Site”—A Tale of Four Stoves from the 1845 Franklin Northwest Passage Expedition - Stenton, Douglas R.; Park, Robert W. (ARCTIC, 2020)
Few detailed analyses exist for the majority of the sites that comprise the archaeological record of the 1845Franklin Northwest Passage expedition. This paper presents the results of new investigations of an Inuit site (NgLj-9) at Erebus Bay on King William Island, Nunavut, containing materials derived from the 1845 Franklin expedition. The complex history of the origin and use of artifacts found at the site and its relationship to other Franklin sites and events associated with theexpedition are revealed through the analysis and integration of archaeological, historical, and oral historical data. Il existe peu d’analyses détaillées pour la majorité des sites qui composent les données archéologiques del’expédition du passage du Nord-Ouest de Franklin en 1845. Dans ce document, nous présentons les résultats de nouvelles enquêtes relatives à un site inuit (NgLj-9) situé à la baie d’Erebus de l’île King William, au Nunavut. Ce site renferme du matériel dérivé de l’expédition Franklin en 1845. L’histoire complexe de l’origine et de l’utilisation des artefacts trouvés au site de même que son lien avec les autres sites et événements liés à l’expédition Franklin sont révélés par le biais de l’analyse et del’intégration des données archéologiques, historiques et orales historiques.